Evaluasi Shift Kerja dan Penentuan Waktu Standar PT X Berdasarkan Beban Kerja - Trisna Mesra; Lusi Susanti; Hilma Raimona Zadry (Jurnal Optimasi Sistem Industri, 2016)
PT. X is one of the companies located in Dumai Industrial Region, produces fertilizer. This company has three production plants. The production capacity of the first plant is 450 tons/day, the second plant produces 750 tons/day and the third plant produces 700 tons/day. PT. X is supported by 2 sub companies, they are PT. A and PT. B. PT. A operates 5 bagging lines and PT. B operates 3 bagging lines. The fertilizer bagging process has three steps where each step has its own work station: putting the labeled sack to the hook followed by filling the sack with fertilizer, installing the tie cable, and sewing the fertilizer filled sack. From the initial survey, it was found that the processing time is not optimal to reach production target. PT. A and B have to set 24 working hours per day to run the target resulting on frequent over time, excessive fatigue and the negative impact of physically and mentally for the workers. Author’s hypothesis is the current condition has been one of the reasons for a decline of the production output. Therefore, the purposes of the research are to find the impact of current working hours and shift work pattern on the physical and psychological response of the workers and to calculate the standard time required to complete one cycle of bagging process. This standard time is very crucial to determine production target thus determine the optimal working hours and shift rotation. Measuring of heart rate are collecting results of a questionnaire of NASA-TLX are the parameters used to evaluate the physical and psychological response of workers. Two workers from different group worker, different shift work, from PT. A and PT. B were selected as samples to evaluate their heart rate pattern. The questioner spread out to all workers. Time standard was determined by observing and taking data of 40 bagging cycles for each shift work. The results show that shift work affecting the physiological response of workers in PT. B in the category between moderate to extreme especially for working element of arranging fertilizer sack to the pallet. This result was found for the two group workers. Frequent short rests between times are required to provide quick recovery for the workers and reduce excessive fatigue. Average standard time complete one bagging cycle was 0.12 minutes and 0.13 minutes for PT. A and PT. B, respectively. These standard times can be used to set the production output target for the two companies. Last, short rotation shift work with an additional number of workers is recommended for the shift pattern